Increased SOAT2 expression in aged regulatory T cells is associated with altered cholesterol metabolism and reduced anti-tumor immunity - Mingjiong Zhang; Jiahua Cui; Haoyan Chen; Yifan Cheng; Qiaoyu Chen; Feng Zong; Xiao Lu; Lang Qin; Yu Han; Xingwang Kuai; Yuxing Zhang; Minjie Chu; et al. (Nature Communications)
Abstract Immune functions decline with aging, leading to increased susceptibility to various diseases including tumors. Exploring aging-related molecular targets in elderly patients with cancer is thus highly sought after. Here we find that an ER transmembrane enzyme, sterol O-acyltransferase 2 (SOAT2), is overexpressed in regulatory T (Treg) cells from elderly patients with lung squamous cell carcinoma (LSCC), while radiomics analysis of LSCC patients associates increased SOAT2 expression with reduced immune infiltration and poor prognosis. Mechanically, ex vivo human and mouse Treg cell data and in vivo mouse tumor models suggest that SOAT2 overexpression in Treg cells promotes cholesterol metabolism by activating the SREBP2-HMGCR-GGPP pathway, leading to enhanced Treg suppresser functions but reduced CD8+ T cell proliferation, migration, homeostasis and anti-tumor immunity. Our study thus identifies a potential mechanism responsible for altered Treg function in the context of immune aging, and also implicates SOAT2 as a potential target for tumor immunotherapy.